A Brief Review on Gestational Diabetes Mellitus - Somwanshi, Sachin B.; Kotade, Kiran B. (Technological Innovation in Pharmaceutical Research Vol. 4, 2021)
GDM (gestational diabetes mellitus) is a common metabolic condition that manifests itself in varying degrees of severity before or during pregnancy. It has been linked to negative maternal and newborn outcomes. Globally, the prevalence of GDM is rising, along with the rise in the incidence of obesity and type 2 diabetes mellitus. It is critical to detect and treat GDM as soon as possible in order to minimise or eliminate difficulties for both the mother and the foetus. Globally, there is indeed a lack of consistency in evaluating and detecting GDM. This article discusses the most recent developments in the diagnosis and treatment of GDM. For the greatest outcomes, treatment must be tailored to the person, combining medical nutrition therapy, supplemental food, and exercise. If these strategies fail to regulate blood glucose levels, pharmacologic therapies, namely insulin and its analogues, should be implemented. The treatment with pharmacologic interventions has an important role on lowering the complications related to GDM. Other oral antihyperglycemic drugs like Metformin and Glyburide are also considered in light of emerging information about their safety and efficacy during pregnancy.